Courses Storage and Retrieval - Castro Alpízar, Roxana (1992)
Roxana Castro Alpízar of the School of Library, Documentation and Information of the National University of Costa Rica presents her paper with the theme "The Management of Information in Specialized Areas in Costa Rica".